"Whatever it takes": first budgetary responses to the COVID-19 pandemic in France. Issue 1 (3rd November 2020) - Cho, Charles H.; Jérôme, Tiphaine; Maurice, Jonathan
Abstract : Purpose: This paper highlights the emergency budgetary measures taken by the French government in response to the COVID-19 pandemic health crisis and identifies some of the key political, economic, social and environmental factors and consequences associated with those measures. Design/methodology/approach: The authors conduct a thorough analysis of official reports, bills and academic and news articles related to the pandemic management in France. The authors' analysis covers the period from January 24 to July 31, 2020. Findings: Despite previous austerity policies, France faced the health crisis with a very high level of debt, which has complicated the management of the COVID-19 crisis. Although significant, the response brought by the French government seems in the end to be rather choppy. Originality/value: This paper highlights three elements of analysis that allow a better understanding of the budgetary management process in France. The authors first discuss the notion of budgetary flexibility. Then, they show that the growth of participatory budgets in local communities gives hope for a possible and much needed decentralization process implying a stronger commitment of citizens. Finally, they highlight a budgetary paradox; that is, massive funding of polluting industries versus ecological issues. These three elements of analysis all advocate the need for a deeper engagement among different levels of government and actors.